Analisis Learning Loss Pasca Pandemi Covid-19 pada Siswa Kelas IV SDN 110 Pekanbaru - Nada, Ferdhiati; Erlisnawati, Erlisnawati; Munjiatun, Munjiatun (Darul Yasin Al Sys, 2023)
The aim of this research is to analyze learning loss after the Covid-19 pandemic in class IV students. This research was carried out at SDN 110 Pekanbaru. The subjects in this research were all class IV C students at SDN 110 Pekanbaru, totaling 36 students consisting of 20 men and 16 women. Data analysis used quantitative methods and a descriptive approach. From the results and discussion, it can be concluded that the subjects studied experienced learning loss due to: 1) Prolonged interaction gaps, learning concentration was disturbed due to studying while helping parents and home conditions that were not conducive, as well as the learning material being incomplete, so that the level of students' absorption of the material to decrease; 2) Science and technology are not evenly distributed among students and parents in using online media; 3) Bad habits during distance learning, such as many students not paying attention when the teacher explains the material, students not focusing when studying in class, students delaying doing and submitting assignments, and the decline in students' enthusiasm for learning is still carried over when face-to-face learning is carried out again; 4) Never have discussions during distance learning so you cannot exchange ideas with colleagues. This has the impact of making it difficult to follow more complex material in class IV because of the decline in mastery of basic skills when sitting in class III.